PENDEKATAN FORMULASI STRATEGI TEKNOLOGI DALAM INDUSTRI KECIL MODERN UNTUK MENINGKATKAN DAYA SAING - Yohanes Tri Joko Wibowo; Totong Totong (Politeknik Manufaktur Astra, 2012)
Technological development is rapidly increasing, pushing the company indirectly to utilize the technology. The technology that the company uses, both of which are directly involved in the operational activities of the company and the supporters, will improve the company capabilities. In the technology era, company capabilities is the capability to respond positively to the dynamic current situation. Today, small industry is no longer a small industry in all matter, but it has a major role in maintaining the stability of the national economy through an empowerment environment process . The role of small industry in promoting economic growth environment is no longer in doubt. By these reasons, small industries should be given a clear reference to the role of technology for them and how to approach technology can help small industry for more advanced and developed in the middle of the competition. Described in this paper technological approach in a technological strategy to help self-assessment process to improve competitiveness and increase the ability of small industrial.